Navigating the New Normal: Investigating Post-Pandemic Pedagogical Shifts and Generation Z Learning Dynamics through the Lens of Educators - Dr. Hafiz Muhammad Arshad; Mirza Muhammad Ali Raza (Journal of Religion and Society, 2025)
The COVID-19 pandemic severely shook the world of education and the sudden shift to emergency remote and hybrid teaching unveiled inequities and speeded up the pace of pedagogical innovations. As a qualitative study, it follows a phenomenological approach and explores the post-pandemic pedagogical changes and matches them with the dynamics of learning among Generation Z (born 1997-2012) under the views of teachers. Based on semi-structured interviews of 18 experienced educators at the secondary and higher education level, the study refers to long-term transformations, including hybrid/flexible models, AI-enhanced customization, asynchronous choice, gamification, and socio-emotional focus. Gen Z is characterized by an increased level of digital fluency and the lack of interpersonal soft skills, motivation issues, and increased values on mental health, work-life balance, and purpose-driven learning. Teachers share adaptive approaches such as student-centered approaches, mental health interventions, and technology-based innovation which brought an engagement benefit but also the tension resulting in increased workloads, burnout, and some equity obstacles. Examples of success point to resilience and empathy building possibilities, whereas the recommendations include specific professional development, institutional support and policy changes that would allow maintaining inclusive practice. The research addresses a critical gap of educators lived experience focus to enable equitable, dynamic education in the new normal, which provides informational contribution to bridging between generational needs and long-term pedagogical change and development of a future-oriented learning environment. Keywords: Post-Pandemic Education, Generation Z, Pedagogical Shifts, Educators' Perspectives, Hybrid Learning, Socio-Emotional Learning